Dabigatran etexilate for the treatment of acute venous thromboembolism in children (DIVERSITY): a randomised, controlled, open-label, phase 2b/3, non-inferiority trial. Issue 1 (January 2021) - Halton, Jacqueline; Brandão, Leonardo R; Luciani, Matteo; Bomgaars, Lisa; Chalmers, Elizabeth; Mitchell, Lesley G; Nurmeev, Ildar; Sharathkumar, Anjali; Svirin, Pavel; Gorbatikov, Kirill; Tartakovsky, Igor; Simetzberger, Monika; et al.
Summary: Background: Dabigatran etexilate is a direct oral anticoagulant with potential to overcome the limitations of standard of care in children with venous thromboembolism. The aims of this clinical trial were to study the appropriateness of a paediatric dabigatran dosing algorithm, and the efficacy and safety of dabigatran dosed according to that algorithm versus standard of care in treating children with venous thromboembolism. Methods: DIVERSITY is a randomised, controlled, open-label, parallel-group, phase 2b/3 non-inferiority trial done in 65 centres in 26 countries. Standard of care (low-molecular-weight heparins, unfractionated heparin, vitamin K antagonists or fondaparinux) was compared with a paediatric oral dabigatran dosing regimen (an age-adjusted and weight-adjusted nomogram) in children younger than 18 years with acute venous thromboembolism initially treated (5–21 days) with parenteral anticoagulation, requiring anticoagulation therapy for at least 3 months. Patients were randomised 1:2 (standard of care:dabigatran) and stratified by age (12 to <18 years, 2 to <12 years, and birth to <2 years) via interactive response technology. The primary composite efficacy endpoint (intention-to-treat analysis) was the proportion of children with complete thrombus resolution, and freedom from recurrent venous thromboembolism and venous thromboembolism-related death. A non-inferiority margin of absolute differences of 20% was used. Secondary endpoints included safety (determined by major bleeding events [time-to-event analysis on the treated set]), and pharmacokinetic–pharmacodynamic relationships (descriptive analyses). This trial is registered with ClinicalTrials.gov, NCT01895777 and is completed. Findings: 328 children were enrolled between Feb 18, 2014, and Nov 14, 2019. 267 were randomly assigned (90 [34%] to standard of care and 177 [66%] to dabigatran) and included in the analyses. Median exposure to standard of care was 85·0 days (IQR 80·0–90·0) and to dabigatran was 84·5 days (78·0–89·0). Similar proportions of children treated with standard of care and dabigatran met the composite efficacy endpoint (38 [42%] of 90 vs 81 [46%] of 177; Mantel-Haenszel weighted difference, −0·04; 90% CI −0·14 to 0·07; p<0·0001 for non-inferiority). On-treatment bleeding events were reported in 22 (24%) of 90 children receiving standard of care and 38 (22%) of 176 children receiving dabigatran (hazard ratio [HR] 1·15, 95% CI 0·68 to 1·94; p=0·61); major bleeding events were similar between the groups (two [2%] of 90 and four [2%] of 176; HR 0·94, 95% CI 0·17 to 5·16; p=0·95). Pharmacokinetic–pharmacodynamic curves showed a linear relationship between total dabigatran plasma concentration and diluted thrombin time and ecarin clotting time, and a non-linear relationship with activated partial thromboplastin time; curves were similar to those for adults. Serious adverse events were reported for 18 (20%) of 90 children receiving standard of care and 22 (13%) of 176 children receiving dabigatran. The most common severe adverse events were vascular disorders (standard of care three [3%] of 90, dabigatran two [1%] of 176), and gastrointestinal disorders (standard of care two [2%] of 90 and dabigatran five [3%] of 176). One on-treatment death occurred in the standard of care group (retroperitoneal bleeding, not considered treatment related by the study investigators). Interpretation: An age-adjusted and weight-adjusted dabigatran dosing algorithm was appropriate in children aged birth to less than 18 years with venous thromboembolism. Dabigatran was non-inferior to standard of care in terms of efficacy, with similar pharmacokinetic–pharmacodynamic relationships as those seen in adults, and might be a suitable alternative to standard of care. Funding: Boehringer Ingelheim.